Acute Brucella infection associated with splenic infarction: a case report and review of the literature - Shi, Limei; Wang, Shuang; Li, Xiaohua; Li, Xin; Li, Yuxiang; Wang, Yang (Frontiers in Cellular and Infection Microbiology, 2023)
Brucella infection often involves multiple organ systems with nonspecific clinical manifestations, and cutaneous involvement is uncommon. Splenic infarction and leukocytoclastic vasculitis also rarely occur together in the course of brucellosis infection. We report the case of a 47-year-old male with Brucella combined with splenic infarction. The patient presented with fever and large liver, spleen, and lymph nodes with muscle and joint pain, positive laboratory tests for blood cultures（Brucella abortus）, and imaging suggestive of splenic infarction. After treatment with streptomycin, doxycycline, and rifampicin, the patient's clinical symptoms and splenic damage improved. Detailed history taking, correct interpretation of laboratory results and knowledge of rare complications of human brucellosis facilitate early diagnosis and treatment of the disease.